SURVEI KEJADIAN FILARIASIS PADA MASYARAKAT DESA TAWANGREJO KUNDURAN BLORA - Didik Sumanto; Sri Sinto Dewi (JURNAL LITBANG, 2006)
Background : On April 2005, DKK Blora found fourteen peoples that infected by elephanthiasis (/ilariasis) in Blora Central of Jawa. Tofollow up this discovery, DKK Blora do thefilariasis surveyfor 500 peoples andfound 163 peoples (48 o/o) wilh posilif filariasis infection.Objective : To do the repetition survey and tell the filariasis incident on society of Tawangrejo, Kunduran, Blora.Research method : The population of this resesrh is all of the people of Tawangrejo Blora